MANAJEMEN PENDIDIKAN ISLAM DALAM PENINGKATAN KEDISIPLINAN SANTRI PONDOK PESANTREN AL-HASAN KAWASEN BANJARSARI CIAMIS JAWA BARAT - Mulyadi A. (UNISAN JURNAL, 2024)
This research aims to identify the leadership style applied by the principal at SD Negeri 04 Sungai Gadiang in improving teacher professional competence, as well as to determine the factors that influence the application of this leadership style and its impact on increasing teacher competence. The research method used was a descriptive qualitative approach with research subjects including school principals and teachers at SD Negeri 04 Sungai Gadiang. The data collection techniques used were observation, interviews and documentation studies. The research results show that the principal at SD Negeri 04 Sungai Gadiang applies various leadership styles, such as transformative, democratic, transformational, and instructional, to improve teachers’ professional competence. Factors that influence the application of this leadership style include transformational, instructional, situational and democratic leadership. The impact of implementing the principal’s leadership style on increasing teacher professional competence includes increasing teacher motivation, better teaching skills, improving the quality of learning, increasing teacher performance, and increasing student learning achievement. In conclusion, the principal’s leadership plays a very important role in improving teacher professional competence and the quality of education at SD Negeri 04 Sungai Gadiang. Therefore, it is recommended that school principals continue to develop their leadership abilities in accordance with the demands of the times and school needs, as well as paying more attention to developing teacher competency to improve the quality of education in the school. Keywords: